Relative efficacy and safety of simeprevir and telaprevir in treatment‐naïve hepatitis C‐infected patients in a Japanese population: A Bayesian network meta‐analysis. Issue 10 (3rd March 2015) - Quigley, Joan M.; Bryden, Peter A.; Scott, David A.; Kuwabara, Hiroyo; Cerri, Karin
Abstract : Aim: Simeprevir (SMV) is an oral, once‐daily protease inhibitor for the treatment of chronic hepatitis C virus (HCV) genotype 1 infection. In phase II/III randomized controlled trials (RCT) conducted in Japan, SMV, in combination with peginterferon‐α and ribavirin (PEG IFN/RBV), demonstrated potent efficacy in HCV genotype 1‐infected patients relative to PEG IFN/RBV and was generally well tolerated. Telaprevir (TVR) in combination with PEG IFN/RBV is licensed for the treatment of HCV in Japan. In the absence of head‐to‐head comparisons of TVR and SMV in a Japanese population, we undertook a network meta‐analysis (NMA) to examine the relative efficacy and safety of SMV and TVR in combination with PEG IFN/RBV. Methods: A systematic review identified SMV and TVR RCT in Japanese treatment‐naïve patients. Bayesian NMA was performed assuming fixed study effects. Results: Three studies met our inclusion criteria: two SMV and one TVR. SMV showed a higher mean odds ratio (OR) of achieving SVR versus TVR (OR, 1.68 (95% credible interval 0.66–4.26)). SMV showed a lower mean OR of discontinuation: overall, 0.35 (0.12–1.00); and due to AE, 0.87 (0.23–3.34) versus TVR. SMV showed a lower mean OR of experiencing anemia 0.20 (0.07–0.56) and rash 0.41 (0.17–0.99) but a higher mean OR of experiencing pruritus 1.26 (0.46–3.47) versus TVR. Conclusion: In this indirect treatment comparison, SMV, in combination with PEG IFN/RBV, showed a favorable risk–benefit profile compared with TVR with PEG IFN/RBV in Japanese treatment‐naïve HCV patients.